Prevalence of the amyloidogenic transthyretin (TTR) V122I allele in 14 333 African–Americans. (September 2015) - Jacobson, Daniel R.; Alexander, Alice A.; Tagoe, Clement; Buxbaum, Joel N.
Abstract Background: Transthyretin (TTR) V122I (rs76992529) is one of 111 variants caused by point mutations in the coding sequence of the human TTR gene that are associated with systemic amyloidosis. It results from a G to A transition at a CG dinucleotide in codon 142(122 of the mature protein) of the gene and has been described almost exclusively in people of African descent. Several series have reported allele frequencies from 0.015 to 0.020 in African-Americans. Objective: To define more accurately the frequency of the TTR V122I variant allele in the African-American population. Methods: DNA isolated from blood spots from 1688 New York State African-American newborns was genotyped for the TTR V122I allele. We also compiled new data from the Jackson Heart Study and previously unpublished data from the Dallas Heart Study, plus data from a San Diego "wellness study", providing 15 650 additional allelotypes to those already reported. Results: Among the New York newborns, the TTR V122I allele was present in 65/3376 alleles (allele prevalence 0.0193). The combined available data from all the non-selected African-American cohorts showed the TTR variant allele to be present in 451/26 062 alleles (allele prevalence of 0.0173), slightly but not significantly lower than our previously published estimates. Conclusions: The allele prevalence for TTR V122I in African-Americans is 0.0173. Of African–Americans under age 65, 3.43% carry at least one copy of the variant amyloidogenic allele.